The role of Tourism clusters on regional competitiveness ( Case study: Religious tourism cluster of Qom) - Abolfazl Moarefi; Arash Sadri; Hadi Gholami Norabad; behzad saeidi (تحقیقات کاربردی علوم جغرافیایی)
As a novel idea for discussion on the role of industrial development on regional development, the term “cluster” became noteworthy since 90’s in order to increase competitiveness. Territorial development researchers believe that formation of regional industrial clusters improves competitiveness and plays a role in promoting competitive advantages and regional development. Hence, because of the possibility of realization of competitive advantage, Tourism clusters became a focal point for research and policy making. Against this background, the purpose of this research is to analyze and review the role of industrial clusters on development of regional competitiveness and assumes that the higher number of relations in an industrial cluster leads to higher level of regional competitiveness. The research applies descriptive-analytical research method and utilizes questionnaire to collect data. The data was studied by SPSS and Lisrel software packs after approval of validity and reliability of data. Findings corroborate the relation between higher number of relations in industrial clusters with higher level of regional competitiveness and also identifies the contributing factors to development and stimulation of regional development which are ranked by the order of their effect as follows: 1. Social relations, 2. Geographic and location relations, 3. Economic relations, and 4. Institutional relations.